22nd Annual IHI Scientific Symposium on Improving the Quality and Value of Health Care. Issue 12 (18th November 2016) - Parry, Gareth
Abstract : Background: Hosted by the Institute for Healthcare Improvement (IHI), the 22nd Annual Scientific Symposium on Improving the Quality and Value of Health Care takes place on Monday, December 5, 2016, in Orlando, Florida, USA. The Scientific Symposium aimed to attract high quality, scientific work, focused on the improvement of health and health care. The Symposium also aimed to foster dialog and share learning among participants. The day features keynote speakers, methods sessions, poster presentations and oral presentations. The 32 oral presentations were selected from 154 abstract submissions, through a process peer review process, that ensured each abstract was reviewed by four reviewers. For those authors that gave permission, the abstracts of the selected oral presentations are published in this supplement. Acknowledgments: On behalf of the Institute for Healthcare Improvement, the hosts would like to thank the individuals whose contributions have made the 22nd Annual Scientific Symposium on Improving the Quality and Value of Health Care a success. Particular thanks are due to the abstract reviewers – Amrita Dasgupta, Anne Lambert-Kerzner, Anup Patel, Barry Appleton, Brant Oliver, David Williams, Don Goldmann, Edahrline Salas, Evie Alessandrini, Fiona Levy, Gareth Parry, Jane Roessner, Jon Finkelstein, Kedar Mate, Linson Naval, Lisa Cosimi, Lisa Rubenstien, Lloyd Provost, Mara Laderman, Marianne McPherson, Nana Twum-Danso, Natalie Henrich, Pierre Barker, Sandy Cohen, Sharon Muret-Wagstaff, A. J. Layon, Andrew Steele, Angela Green, Darren Klugman, David Mosen, Denise Remus, Ezequiel Garcia Elorrio, Jackie Valentine, Keith Mann, Mary Coleman, Omar Hasan, Rick McClead, Sandip Godambe, Thomas Bartman, Tina C. Foster, Uma Kotagal, and Wallace Crandall – without whose efforts we could not accomplish a Symposium of this quality. Thanks, as well, are due all those who were willing to submit their research for review. Last, but certainly not least, we thank our program committee members – Don Goldmann, Pierre Barker, Amy Reid, Beth McGlynn, John Finkelstein, Lisa Hirschhorn, Rohit Ramaswamy, Elizabeth McGlynn, Sabrina Selk, Rashad Massoud, Margee Louisias, Lloyd Provost, Laura Damschroder, Uma Kotagal, and Marianne McPherson – who provided valuable insight and guidance to make this year's Symposium as enriching as possible; and Amrita Dasgupta, Jason Reed and Linson Naval who have dedicated countless hours to the development of this year's program.